Identificación de técnicas de manufactura y funcionalidad de vasijas cerámicas en estudios de lámina - Capel Martínez, Josefa; Guardiola, J.L.; Delgado Calvo Flores, R.; Párraga, J. (Complutum, 1995)
Sin resumen